Phase processing techniques for the prediction of induced current - Wraight, Anthony; Morrow, Ivor L.; Robinson, John; Marino, Michael; Marson, Roger (IEEE, 2008)
This paper reviews the currently used minimum phase algorithm approach for the prediction of induced current as a result of the incidence of a time-domain electromagnetic environment such as an electromagnetic pulse. An alternative to this approach is proposed that enables the user to identify a lower bound on the minimum phase prediction. The technique has been applied to over 500 transfer functions with three different high-power electromagnetic environments and the results are presented and discussed within this paper. The paper concludes that the proposed method is a useful technique in providing an alternative method of predicting the induced current.
Keywords: electromagnetic pulse (EMP); high-power electromagnetic (HPEM); phase; signal processing; 4006 Communications Engineering; 40 Engineering; 4008 Electrical Engineering; 4.1 Discovery and preclinical testing of markers and technologies; Networking & Telecommunications; 4009 Electronics, sensors and digital hardware